The Effect of Sales and Total Debt on the LQ45 Company’s Stock Price on the Indonesia Stock Exchange for the 2021-2022 Period - Wasserbauer, Michal (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
This study aims to see the effect of sales and total debt on stock prices in LQ45 companies listed on the Indonesian Stock Exchange from February to July 2022. The independent variables in this study include: sales and total debt, with the dependent variable, namely stock price. The data used in this study are secondary data, obtained from the Indonesian stock exchange. The sampling technique uses simple random sampling. The population of this study is 45 companies listed on the LQ45 IDX for the period August 2021 – July 2022. The total sample size is 20 companies listed on the LQ45 IDX and come from various industrial sectors. Tests performed t test, f test, and the coefficient of determination r-square. Where secondary data has been tested for validity and reliability, and classical assumption tests have been carried out and all data meets to continue analysis or data processing. The company's financial data used covers the years 2021-2022 on the Indonesian stock exchange. Data processing uses the IBM SPSS version 27 data processing application. The results of this study indicate that sales partially affect the stock price of LQ45 companies on the IDX for the 2021-2022 period, total debt has no effect and is not significant on the stock price of LQ45 companies on the IDX for the 2021-2022 period partially, and sales and total debt have no effect and are not significant on the stock price of LQ45 companies on the IDX for the 2021-2022 period simultaneously.